Enzyme-displaying spores as a novel strategy for mixed fiber textile recycling - Matti Lehmann; Max Herrmann (Frontiers in Systems Biology)
Global textile manufacturing practices are responsible for an increasing amount of textile waste that pollutes our planet. Mixed fiber blends pose a recycling challenge due to their heterogeneous structure. Current mechanical, chemical, thermochemical and enzymatic strategies suffer from several limitations such as high energy costs, extensive pre-treatment requirements and enzyme instability. This mini-review aims to present recent developments in the research field and to introduce Spore Surface Display (SSD) technology as a new biological approach for mixed textile degradation. SSD allows enzymes to be anchored on the robust bacterial spore surface, immobilizing multiple enzymes required for simultaneous cotton-polyester degradation into their respective monomers. The mini-review also includes an initial proposal for a process design suitable for a full mixed textile degradation process using this synthetic biology approach.